Peripheral blood iNKT cells display an activated profile with both increased apoptosis and dysfunction in obesity - Wilkin, Chloé; Esser, Nathalie; Lassence, Cédric; Bruneteaux, Marion; Fadeur, Marjorie; De Flines, Jenny; Paquot, Nicolas; Piette, Jacques; Legrand-Poels, Sylvie (Frontiers in Immunology, 2025)
Obesity is characterized by a chronic low-grade inflammation and, paradoxically, is also associated with immune cells dysfunction. In this study, we analyzed peripheral blood Invariant Natural killer T cells (iNKT) in individuals with or without obesity. These unconventional T cells recognize lipid antigens presented by the monomorphic CD1d MHC I-like protein. We demonstrated an activation of iNKT cells in individuals with obesity associated with both increased apoptosis and dysfunction as assessed by the lack of responsiveness to PMA/Ionomycin stimulation. This disruption mainly affects the CD4− subset, more dedicated to pro-inflammatory cytokines release and cytotoxicity. Such impact could therefore be involved in the loss of immunosurveillance observed in obesity. Interestingly, CD1d is upregulated on intermediate and non-classical monocytes from individuals with obesity and its expression on both monocyte subsets is correlated with iNKT cell dysfunction. Both the activation and hypo-responsiveness of iNKT cells as well as CD1d modulation on monocytes are significantly reversed after bariatric surgery. Altogether, these data suggest that increased CD1d expression may enhance the presentation of endogenous lipid antigens, thereby contributing to iNKT cell activation in the context of obesity.